2019
DOI: 10.3892/ol.2019.10073
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value analysis of combined detection of Trx, CYFRA21-1 and SCCA in lung cancer

Abstract: The expression levels of thioredoxin (Trx), cytokeratin fragment 21–1 (CYFRA21-1) and serum squamous cell carcinoma antigen (SCCA) in patients with lung cancer and the diagnostic value of combined detection were investigated. Sixty-five patients with lung cancer in Weihai Municipal Hospital from January 2014 to June 2017 were retrospectively selected as the observation group, while 60 healthy subjects receiving physical examination were selected as the control group. The expression levels of serum Trx, CYFRA21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…With more and more extensive research, it has been found that up‐regulated SCCAg in serum is similarly observed in many malignant tumors such as hepatocellular carcinoma, 29 small cell lung cancer, 13 and esophageal cancer 14 . Among oral malignancies, it has been reported that serum SCCAg levels increase sequentially in the control, OPMD, and OSCC groups 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With more and more extensive research, it has been found that up‐regulated SCCAg in serum is similarly observed in many malignant tumors such as hepatocellular carcinoma, 29 small cell lung cancer, 13 and esophageal cancer 14 . Among oral malignancies, it has been reported that serum SCCAg levels increase sequentially in the control, OPMD, and OSCC groups 30 .…”
Section: Discussionmentioning
confidence: 99%
“…It often exists in normal squamous epithelial cells but is increased in the serum and tissues of epithelial malignant tumors 12 . Recently, SCCAg has been explored as a biomarker for various malignant diseases such as lung cancer, 13 esophageal cancer, 14 head and neck cancer, 15 and cervical cancer, 16 and has also been explored as a prognostic biomarker for OSCC 17 . A previous study found that SCCAg was elevated in patients with lichen planus and related to the severity of the disease, 18 indicating that it may have a role in the diagnosis and prognosis of OPMDs.…”
Section: Introductionmentioning
confidence: 99%
“…The value of the detection of single markers for identifying patients with lung cancer is low; therefore, many others have identified combinations of TAA biomarkers that are useful for detecting LC. Most recently, Qu et al [ 20 ] (Qu, Zhang et al 2019) showed that the combination of thioredoxin (Trx), CYFRA21-1, and SCC biomarkers can improve both specificity and sensitivity to diagnose lung cancer patients from healthy subjects. Jiang et al [ 21 ] (Jiang, Wang et al 2018) investigated a combination of CEA, CYFRA21, NSE, and thymidine kinase 1 (TK1) for lung cancer diagnosis; the results showed that the diagnostic value of TK1 combined with CEA, CYFRA21-1, and NSE was significantly higher than that of each biomarker alone.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the diagnostic accuracy and avoid unnecessary invasive procedures, it was necessary to combine tumor markers with imaging. The conventional serum biomarkers for lung cancer included cytokeratin 19 (CYFRA21‐1), pro‐gastrin‐releasing‐peptide (ProGRP), carcinoembryonic antigen (CEA) neuron‐specific enolase (NSE), and squamous cell carcinoma‐associated antigen (SCCA) 10,11 . Study 12 indicated that for solitary pulmonary lesions, using the tumor markers alone, the highest sensitivity (27.2%) and accuracy (40.4%) were found with CEA, the highest specificity (100%) with CYFRA 21‐1, and with NSE.…”
Section: Introductionmentioning
confidence: 99%